Upaya Guru dalam Meningkatkan Karakter Disiplin Siswa di SMK Negeri 1 Siau Timur Kabupaten Sitaro - Intan Pinasty Tamalumu; Apeles Lexi Lonto; Isye Junita Melo (CV. Kurnia Grup, 2026)
This study aims to find out why students at SMK Negeri 1 East Siau are still found to have less disciplined behavior and to find out teachers' efforts to improve the disciplinary character of SMK Negeri 1 Siau Timur students. The research method used is qualitative with a case study approach. The results of the study show that lack of discipline behavior is still found in some students in daily life in the school environment. The first factor is the low awareness of students on the importance of discipline is one of the main causes. There is also a factor of lack of personal responsibility as a student should be reflected in the attitude of carrying out learning obligations, obeying regulations, in addition to that there is also a factor of influence on the peer environment, at the age of adolescence students tend to be more easily influenced by their social groups. The desire to be accepted into a group often encourages students to conform to the prevailing habits within it. If the social environment violates the rules, then students have the potential to follow this behavior. Teachers' efforts to improve the character of student discipline, efforts are made to provide good examples such as arriving on time, dressing neatly, and carrying out tasks with full responsibility.